2014
DOI: 10.4097/kjae.2014.67.5.305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trendelenburg position on right and left internal jugular vein cross-sectional area

Abstract: Background Unlike the right internal jugular vein (RIJV), there is a paucity of data regarding the effect of the Trendelenburg position on the left internal jugular vein (LIJV). The purpose of this study is to investigate the cross-sectional area (CSA) of the LIJV and RIJV and their response to the Trendelenburg position using two-dimensional ultrasound in adult subjects.MethodsThis study enrolled fifty-eight patients with American Society of Anesthesiologists physical status class I-II who were undergoing gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Internal jugular vein catheterization is easy and complications are decreased when cross-sectional area is increased. 14 – 16 Various methods have been attempted to achieve cross-sectional area expansion. The Trendelenburg position is the most preferred because it increases venous return and IJV diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Internal jugular vein catheterization is easy and complications are decreased when cross-sectional area is increased. 14 – 16 Various methods have been attempted to achieve cross-sectional area expansion. The Trendelenburg position is the most preferred because it increases venous return and IJV diameter.…”
Section: Discussionmentioning
confidence: 99%
“…They found that in supine position the CSA of right IJV was larger than the left and also the increase in CSA after 10° Trendelenburg position was larger for right. 2 Increase in CSA is associated with a high success rate of catheterization and less complications. Different maneuvers such as Trendelenburg position, abdominal compression, valsalva, inspiratory hold, PEEP has been used in increase the diameter of the right IJV.…”
Section: Resultsmentioning
confidence: 99%
“…These have proved to increase the diameter of right IJV. [1][2][3][4] The cross sectional area has increased by 72.5% at 15 cm H 2 O PEEP when compared to 0 cm H 2 O PEEP in same patient. 4 Stenosis or thrombosis of right IJV, anatomical changes caused by head and neck surgeries and failure of right IJV catheterization will suggest the catheterization of left IJV be necessary.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Sometimes in our daily routine , we examine children who present with a mass in the neck named flebectasia, which is a widening of this vein. Although there are many studies related to jugular vein diameter in pediatric patients, there are very few studies related to the jugular vein diameter in adults 4,5 .…”
Section: Introductionmentioning
confidence: 99%